Facebook, WhatsApp, and Twitter: Journey towards Education - Alka Singh (Politeknik Negeri Bali, 2018)
Social Media has become a routine activity for everyone. Today’s digital citizens use to start their day with the notifications and end up by checking the newsfeeds on these sites. People use to celebrate important events of life, celebrate the festivals, create and participate in events, show their mood and reflect their thoughts and beliefs on these sites. Thus, Social Networking Sites (SNSs) have become the necessary part of life which cannot be separated from social, professional, academic or individual life. Social media originated strictly as a personal tool to communicate with people around, such as friends and family, but the innovative technology advancements paved the way to use web-based and mobile technologies to turn communication into interactive conversation. Through the present paper, the author tried to explore the features of selected social media, suitable for integrating these in education on the basis of a review of the previous studies and literature available. For the purpose, Facebook, WhatsApp and Twitter have been selected considering their popularity and relevance in the teaching-learning process. The paper provides an outlook to motivate teachers and students to use social media wisely and face the possible challenges smartly. It showcases a journey of social media platforms to begin or flourish its path towards education.